The Effect of Lanolin Cream on Treatment of Traumatic Nipples in Breastfeeding Mothers: A Randomized Control Trial - Shahnazi, Mahnaz; Pourasad Shahrak, Shakiba; Fartash, Fereshteh; Fashbaf Khalili, Azizeh; Masoudin, Kazhal (Advances in Nursing & Midwifery, 2021)
Abstract Introduction: Nipple problems are the most important reason for early cessation of breastfeeding among mothers. Considering the high prevalence of nipple problems, the present study aimed at evaluating the effect of lanolin cream on the treatment of traumatic nipples. Methods: This double-blind randomized controlled trial was carried out on 80 breastfeeding mothers that attend health centers and the children hospital of Sanandaj-Iran. The participants were randomly divided into two groups (lanolin and control). The control group receives all supports of the intervention group but their cream contains colorless and odorless, Gelatinous. Nipple pain and trauma were measured using Storr and Champion scale. Analyses were carried out through the Chi-square, Wilcoxon signed-rank test, and U-Mann Whitney by using SPSS software version 13. Results: There were no significant differences in pain and trauma score before intervention in lanolin and control groups which were (P = 0.336) and (P = 0.21), respectively; but, the results of the study demonstrated that the mean score of pain and trauma in the third, seventh and fourteenth days of study in lanolin group was decreased (P < 0.001). In intragroup comparison, there was a significant difference among the mean pain and trauma scores the four times in the lanolin group. Conclusions: According to the results of the study, lanolin cream is an effective, simple, and non-invasive technique with no side effects for prevention and treatment in nipple fissures and pain.